MHC Intratumoral Heterogeneity May Predict Cancer Progression and Response to Immunotherapy - Romero, Irene; Garrido, Cristina; Algarra, Ignacio; Chamorro, Virginia; Collado, Antonia; Garrido, Federico; Garcia-Lora, Angel M. (Frontiers in Immunology, 2018)
An individual tumor can present intratumoral phenotypic heterogeneity, containing tumor cells with different phenotypes that do not present irreversible genetic alterations. We have developed a mouse cancer model, named GR9, derived from a methylcholanthrene-induced fibrosarcoma that was adapted to tissue culture and cloned into different tumor cell lines. The clones showed diverse MHC-I phenotypes, ranging from highly positive to weakly positive MHC-I expression. These MHC-I alterations are due to reversible molecular mechanisms, because surface MHC-I could be recovered by IFN-γ treatment. Cell clones with high MHC-I expression demonstrated low local oncogenicity and high spontaneous metastatic capacity, whereas MHC-I-low clones showed high local oncogenicity and no spontaneous metastatic capacity. Although MHC-I-low clones did not metastasize, they produced MHC-I-positive dormant micrometastases controlled by the host immune system, i.e., in a state of immunodormancy. The metastatic capacity of each clone was directly correlated with the host T cell subpopulations; thus, a strong decrease in cytotoxic and helper T lymphocytes was observed in mice with numerous metastases derived from MHC-I positive tumor clones but a strong increase was observed in those with dormant micrometastases. Immunotherapy was administered to the hosts after excision of the primary tumor, producing a recovery in their immune status and leading to the complete eradication of overt spontaneous metastases or their decrease. According to these findings, the combination of MHC-I surface expression in primary tumor and metastases with host T cell subsets may be a decisive indicator of the clinical outcome and response to immunotherapy in metastatic disease, allowing the identification of responders to this approach.